Prosperity Gospel and Its Religious Impact on Sustainable Economic Development of African Nations - Soboyejo, Josephine O. (Open Access Library Journal, 2016)
Before the advent of African priests, expatriate missionaries in Africa were noted for their detached and abstemious ways of life. They upheld what is known as “Vow of Poverty”, which was taken prior to sacerdotal ordination. They toiled selflessly for their flock without caring for personal material benefits. This orientation has been discarded for prosperity vocation in this 21st century. Priests now use luxurious cars, fly expensive private jets and are escorted by well-armed military/police officers. The social-economy context of prosperity theology has become a great attraction to impoverished people of Africa. The micro and macro economies retrogression in many African nations enable some charismatic and neo-Pentecostal preachers to incorporate prosperity messages into sermons. The doctrine emphasizes the importance of personal empowerment, proposing that it is God’s will for the people to obtain wealth, health and total success in the world. This paper explains the reasons prosperity preaching is hurting Africa; and examines the capitalistic tendencies that have replaced spiritual growth and moral sanctity towards an eternal life. The paper catalogues the religious impact of prosperity gospel on sustainable economic development of African nations. Africa has many Churches; growing rapidly yet remains the only region that poverty has increased in the past two decades. So there is no impact of the prosperity message on the people. Most Africans live on less than $1 a day and many proactive youths are still unemployed. This paper explains how people have been financially exploited, which has led to loss of “Faith” and lack of personal economic security.
free